2023
DOI: 10.1002/ece3.9817
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale movement patterns in a social vulture are influenced by seasonality, sex, and breeding region

Abstract: Quantifying space use and segregation, as well as the extrinsic and intrinsic factors affecting them, is crucial to increase our knowledge of species‐specific movement ecology and to design effective management and conservation measures. This is particularly relevant in the case of species that are highly mobile and dependent on sparse and unpredictable trophic resources, such as vultures. Here, we used the GPS‐tagged data of 127 adult Griffon Vultures Gyps fulvus captured at five differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…This is not surprising as the monogamous Griffon Vulture is sexually monomorphic (Bosé et al 2007), and both sexes equally invest in nesting and parental care (Cramp and Simmons 1982). However, despite what was previously reported (Altea et al 2013, Monsarrat et al 2013), Morant et al (2023) recently found significant differences in movement patterns of breeding Griffon Vultures in different populations in Spain. There, females showed larger home ranges and lower monthly fidelity than males (Morant et al 2023).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is not surprising as the monogamous Griffon Vulture is sexually monomorphic (Bosé et al 2007), and both sexes equally invest in nesting and parental care (Cramp and Simmons 1982). However, despite what was previously reported (Altea et al 2013, Monsarrat et al 2013), Morant et al (2023) recently found significant differences in movement patterns of breeding Griffon Vultures in different populations in Spain. There, females showed larger home ranges and lower monthly fidelity than males (Morant et al 2023).…”
Section: Discussionmentioning
confidence: 78%
“…However, despite what was previously reported (Altea et al 2013, Monsarrat et al 2013), Morant et al (2023) recently found significant differences in movement patterns of breeding Griffon Vultures in different populations in Spain. There, females showed larger home ranges and lower monthly fidelity than males (Morant et al 2023).…”
Section: Discussionmentioning
confidence: 78%
“…Telemetry monitoring confirmed that active breeding individuals have huge home ranges around the colony (Morant et al, 2023). Movements outside the core home range (estimated as the 50% fixed kernel density; Signer et al, 2019) occur sporadically when nestlings were feathered, from about 70 days of age, and lasted for periods of ~1 week (authors' unpublished data).…”
Section: Figurementioning
confidence: 97%
“…Movements outside the core home range (estimated as the 50% fixed kernel density; Signer et al, 2019) occur sporadically when nestlings were feathered, from about 70 days of age, and lasted for periods of ~1 week (authors' unpublished data). When breeding failed, these long‐distance movements become more frequent and long‐lasting, toward the main dispersal area of Iberian nonbreeding griffon vultures in the dehesas of southwestern Spain (Delgado‐González et al, 2022), rarely northward (Morant et al, 2023). Surprisingly, in the last months of the breeding season (June–July) of 2022, a breeding male griffon vulture tracked since June 2021 was absent for a long period from the nest (40 days, from 4 June to 14 July) although it was still raising a nestling (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…This technology has improved the information available on habitats that are important for wild animals, especially for long-lived species [ 11 , 13 ]. Moreover, satellite tracking has clearly showed that even within a species there may be important differences in the use of space, depending on age, sex and seasonality [ 14 , 15 , 16 , 17 ]. Satellite tracking has also made it possible to improve our knowledge on dispersal in several animal species [ 1 , 18 , 19 ], particularly in immature birds [ 6 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%